Memahami Distribusi Spasial Pekerja Migran Berdasarkan Negara Tujuan di Kabupaten Malang - Supriadi, Bambang (Relasi : Jurnal Ekonomi, 2022)
Limited employment opportunities, wage disparities, and consumptive income patterns cause the high labor migration in Malang Regency. This study aims to analyze the spatial distribution of migrants by destination country using data from the Central Bureau of Statistics and interviews. The research method used is the Correlation Matrix of Distribution, which is about the correlation matrix of productive migrant village population. The distribution pattern of the migrant population in each sub-district of Malang Regency is carried out based on the Geographic Information System. The results show that the geographical pattern of the Sumbermanjing Sub-district is the main center for sending migrants. The preference of Taiwan is consistently the leading destination of migrants from all sub-districts. Hong Kong is a significant second choice for interest. Singapore and Malaysia follow this. The pattern shows that economic factors, social networks, and migration policies in destination countries are the main factors in determining the distribution pattern of migrant workers. This research provides insights for policymakers in designing more effective strategies to manage migrant workers and increase the productive use of migration outcomes at the local and national levels.